Probable and confirmed sarcopenia are still better predictors of disability than sarcopenic obesity following ESPEN/EASO consensus steps - Sibel Cavdar; Fatma Ozge Kayhan Kocak; Sumru Savas (BMC Geriatrics)
Abstract Background Studies comparing different operational definitions of sarcopenia (S) and sarcopenic obesity (SO) defined according to the ‘’European Society for Clinical Nutrition and Metabolism and the European Association for the Study of Obesity’’ (ESPEN/EASO) criteria with functionality are scarce. Our aim is to investigate whether SO or S with different skeletal muscle mass (SMM) adjustments is better associated with functional disability. Methods This retrospective study was carried out in older individuals ≥ 65 years of age in a geriatric outpatient clinic. Probable and confirmed sarcopenia were evaluated with the revised European Working Group on Sarcopenia in Older People (EWGSOP2) criteria, and SO with ESPEN/EASO consensus steps. For SMM component for both S and SO, different adjustments (weight, body mass index, and height square (W, BMI, H2 respectively)) were used. Functional disability was examined with activities of daily living (ADL), and instrumental ADL (IADL). Receiver operating characteristic (ROC) curves were drawn and area under ROC curve (AUC) were calculated to find which operational definition best predicts disability. Results Data from 1477 older adults were screened. 408 participants (median age; 73 (65–101), 65% female) were included. Prevelance of SO was 6.9%. Probable sarcopenia, confirmed sarcopenia BMI-adjusted and confirmed sarcopenia W-adjusted were significantly associated with impaired IADL (p < 0.001), and showed fair accuracy for predicting IADL disability. Sarcopenic obesity did not show significant associations with ADL and IADL disability and didn’t predict ADL and IADL disability. Only confirmed sarcopenia by BMI predicted ADL disability with poor accuracy. Among operational definitions of sarcopenia, probable sarcopenia had the highest sensitivity (83.6%) and negative predictive value (NPV) (94.2%) for predicting IADL disability. Conclusion We found that probable sarcopenia (with the highest sensitivity and NPV) and confirmed sarcopenia (BMI-adjusted with higher sensitivity and NPV than W-adjusted) were the most relevant for predicting IADL disability, but their diagnostic accuracy was limited. Confirmed sarcopenia by BMI predicted ADL disability with poor accuracy. Other operational definitions, including SO did not predict functional disability in our study. Future studies need to refine the definitions of SO and investigate its distinct impact on functional impairment compared to sarcopenia alone.